Nationalist language ideologies in tweets about the 2019 Canadian general election. (March 2021) - Vessey, Rachelle
Abstract: Although "bilingualism" (i.e. the official status of English and French) is widely accepted as one of the pillars of Canadian national identity, the number of Canadians reporting a mother tongue other than English or French is rising (Statistics Canada, 2019 ) and there is growing support for Indigenous languages (e.g. Indigenous Languages Act (2019)). The present paper examines the extent to which perceptions of languages in Canada are changing by exploring nationalist language ideologies in tweets during the run-up to the 2019 Canadian general election. A corpus of 123, 058 tweets is examined using a discourse analytic approach to language ideology. Results show that language issues are not a focus of the 2019 general election and metalanguage is relatively infrequent in the dataset. Although evidence of different language ideologies emerges from the data, the overwhelming trend is one of English monolingualism, suggesting reasonable grounds for concern over Canada's other languages.